KONSEKUENSI FINANSIAL KERUSAKAN PREMATUR PERKERASAN JALAN: SEBUAH KERANGKA PIKIR DAN APLIKASINYA - Masinta Simamora; Diarto Trisnoyuwono; Anastasia H. Muda (P3M- Politeknik Negeri Kupang, 2017)
The management of national road is not optimal and has not efficient yet. Its indication is premature damage of road. However, road damage cannot be avoided. The problem is whether premature damage causes losses. This paper aims to show the framework of the losses of premature damage of road in term of financial consequences and to apply that framework by a simulation. Based on concept of benefit value which is represented by serviceability level through pavement condition index for along its life time service was developed the framework of financial consequences on premature damage of road, which is represented with loss of road condition. Second, to count the losses on premature damage of road by a simulation. The result showed that premature damage of road causes lossess. The loss for losing 36 on pavement condition indexs is Rp. 458.257.899,41 per kilo meter. So, the loss for losing one on condition index is Rp. 12.729.386,09. Moreover, in term of the prematur damage is not accured the lose does not arise or zero losses.